Strategies of Maintain the Quality of Cylinary Micro, Small, And Medium Enterprise (MSMEs) - Ajusta, Anak Agung Gede; Ridwan, Wawan; Reptiningsih, Eni; Maharani, Putrie (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Culinary businesses, especially in the MSME sector, face increasing pressure to provide high-quality products that satisfy customers. This study aims to investigate effective strategies in improving product quality in the context of the culinary business. The research method used is a case study with a focus on several MSMEs in the culinary sector that have successfully implemented these strategies. The results of the study indicate that there are several key strategies implemented by MSMEs in improving the quality of their products, including:1. Process Simplification, 2. Detailed Written and Video SOP (Standard Operating Procedure) & SOC (Station Observation Checklists), 3. Routine Training and LMS (Learning Management System), 4. Audit and Mystery Shopper, 5. Routine Consumer Survey, 6. Monitor Review Sites and Social Media, 7. Control Receiving & Storage of Raw Materials, 8. Quality Standards of Raw Materials & Vendors, 9. Supporting Equipment and Supplies, 10. Rules and Culture at Outlets, 11. Reward & Punishment, 12. Outlet Organizational Structure.In addition, the findings also identify challenges faced by MSMEs in implementing these strategies, including high costs for high-quality raw materials, difficulty in finding trained workers, and the need to keep up with changing market trends. The implication of this study is the importance of a holistic approach in managing a culinary business, including the integration of comprehensive quality and service strategies to retain and attract customers. This study contributes to the literature on MSME management by offering practical guidance for culinary business owners to improve their competitiveness through a strong focus on product quality and service.